PENGARUH PENDEKATAN ETNOPEDAGOGI TERHADAP PEMAHAMAN KONSEP DEMOKRASI SISWA KELAS V SDN 6 LABUHAN HAJI - Aulinniha, Mutiara; M.Pd, Zalia Muspita; M.Pd, Rohini; Andi Sulastri, M.Pd (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine the influence of the ethnopedagogy approach on students’ understanding of the concept of democracy. Understanding the concept of democracy is an important part of Civic Education (PPKn), which plays a role in shaping the character of active, critical, and democratic citizens. Based on preliminary observations at SDN 6 Labuhan Haji, it was found that fifth-grade students still experienced difficulties in understanding democratic values such as deliberation, mutual cooperation, and respecting differences of opinion. This was indicated by low learning outcomes and limited student engagement in the learning process. The application of the ethnopedagogy approach, which connects democracy material with the local wisdom of the Sasak community such as the Banjar tradition, beriuk tinjal (mutual cooperation), and the culture of deliberation was carried out as an effort to improve students’ understanding. This research employed a quantitative method with an experimental type and a one-group pretest-posttest research design. Data collection techniques included observation, tests, interviews, and documentation. The research sample consisted of all fifth-grade students at SDN 6 Labuhan Haji, totaling 25 students. The results of the study show that: (1) the implementation of learning using the ethnopedagogy approach was carried out according to the planned stages, as evidenced by the increase in the average pretest score of 58 to a posttest average of 84, categorized as good; (2) there was a significant influence of the ethnopedagogy approach on students’ understanding of the concept of democracy, as indicated by an N-Gain score of 0.60 in the medium-to-high category and the results of the paired sample t-test showing a significance value of 0.000 < 0.05, thus Ha was accepted and Ho was rejected.